Penyadaran Tentang Batasan Hubungan Interaksi Antara Laki – Laki dan Perempuan Terutama Setelah Khitbah (di Dusun Ringinrejo Desa Tiru Lor Kecamatan Gurah Kabupaten Kediri) - Lailatul Maghfiroh Al Maskurin; Siti Kalimah (LP3M IAIFA Kediri, 2021)
Association is the process of interaction carried out by individuals with individuals, can also be done by individuals with groups. Association itself is a fitrah for every human being. Because, basically every human being is a social creature, that does not mean someone can get along with anyone in any way. And in modern times like this social society is often faced with problems that often tarnish religion with an association that is not limited by the rule of law that binds to the adherents of its religion. So it becomes a concern for us Muslims with the habits of people who do not care about the existing rules. Departing from concerns about male and female association in this day and age, the author also carried out socialization activities or awareness about the limitations of relationships (interactions) between men and women according to Islam to several members of IPNU-IPPNU Ringinrejo Village Tiru Lor District Gurah Kediri regency and the brides-to-be who were there. The socialization activities that the author carried out there including considered smooth and successful because they saw the impact of change after the socialization activities were held. I hope it will affect the rest of the environment.